2001
DOI: 10.1074/jbc.m105275200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myosin Phosphatase Isoforms in cGMP-mediated Smooth Muscle Relaxation

Abstract: In vitro experiments showing the activation of the myosin phosphatase via heterophilic leucine zipper interactions between its targeting subunit (MYPT1) and cGMP-dependent protein kinase I suggested a pathway for smooth muscle relaxation (Surks, H. K., Mochizuki, N., Kasai, Y., Georgescu, S. P., Tang, K. M., Ito, M., Lincoln, T. M., and Mendelsohn, M. E. (1999) Science 286, 1583-1587). The relationship between MYPT1 isoform expression and smooth muscle responses to cGMP signaling in vivo has not been explored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
178
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(192 citation statements)
references
References 66 publications
11
178
2
Order By: Relevance
“…M-RIP is thus localized to the contractile filament where myosin light chain phosphorylation regulates the contractile state, suggesting a role for M-RIP in myosin phosphatase regulation. The amino terminus of M-RIP contains adjacent pleckstrin homology domains and polyproline motifs, a structural combination also found on Bruton's tyrosine kinase where it mediates binding to both actin and G␣ 12 (50,51). This region of p116 RIP3 has recently been shown to mediate actin binding and actin bundling activity in vitro (49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…M-RIP is thus localized to the contractile filament where myosin light chain phosphorylation regulates the contractile state, suggesting a role for M-RIP in myosin phosphatase regulation. The amino terminus of M-RIP contains adjacent pleckstrin homology domains and polyproline motifs, a structural combination also found on Bruton's tyrosine kinase where it mediates binding to both actin and G␣ 12 (50,51). This region of p116 RIP3 has recently been shown to mediate actin binding and actin bundling activity in vitro (49).…”
Section: Discussionmentioning
confidence: 99%
“…The carboxyl terminus of MBS contains a leucine zipper domain that mediates binding to other coiled-coil domains, including the leucine/isoleucine zipper domain of cGMP-dependent protein kinase 1␣ (11,12,43). To determine whether this domain of MBS mediates binding to the CC2 of M-RIP, wild-type COOH-terminal MBS (MBS LZ ) and mutant COOHterminal MBS in which all leucines in the leucine zipper domain were mutated to alanine (MBS LZ mutant), were expressed as GST fusion proteins and tested for binding to full-length M-RIP.…”
Section: Detection and Localization Of M-rip In Vascular Smoothmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, our results showed that peroxynitrite treatment induced MYPT1 phosphorylation at both Thr696 and Thr850 in Modulation of MYPT1 abundance and differential expression of spliced variants occurs during development, as well as under physiological and pathological conditions. 9,12,14,15,47,48 In rat uterus, MYPT1 mRNA levels are decreased during the later stages of pregnancy. 15 Hypoxia exposure increases MYPT1 protein levels in the rat aorta.…”
Section: Discussionmentioning
confidence: 99%
“…8 The exclusion of the 31-bp 3 0 exon shifts the reading frame and results in a C-terminal leucine zipper (LZ) motif, while exon inclusion encodes a MYPT1 lacking the LZ motif. 9 In vitro and in vivo evidence showed that the LZ motif present in the C-terminal of MYPT1 is required for the activation of MP by type I PKG. [10][11][12] The sensitivity of smooth muscle to cGMP/PKG-mediated relaxation is proportional to the expression ratio of LZ þ / LZ À MYPT1.…”
mentioning
confidence: 99%